Autonomous Lake Surface Cleaning Machine - Tan, Qi Da; Kok Boon Ching (Evolution in Electrical and Electronic Engineering, 2023)
This paper presents research on the design and development of an autonomous machine for cleaning lake surfaces. The study aimed to solve three main problems: determining the appropriate motor size and body materials, designing an efficient motor control system, and implementing energy efficiency enhancement strategies. To address all problems, extensive analysis and calculations were conducted to select the optimal motor size based on factors such as weight, desired speed, and motor rating. Suitable materials were also evaluated for the machine’s main body to ensure durability and buoyancy in a lake environment. A motor control system using an H-bridge design was developed to enable precise and responsive movement control for autonomous operation and optimized cleaning performance on the lake surface. Furthermore, energy efficiency enhancement strategies, such as utilizing an energy-efficient conveyor system, were implemented in the machine’s design. The results demonstrate the achievement of the research objectives, including appropriate motor sizing and body material determination, efficient motor control system design, and the implementation of energy efficiency enhancement strategies. This encompasses sourcing and procuring components, assembling the main body, taking measurements, and undertaking troubleshooting and refinement efforts on the prototype. The developed machine has the potential to significantly contribute to the maintenance and preservation of lake ecosystems, addressing the environmental challenges associated with lake pollution.